Penerapan Model Pembelajaran Student Teams Achievement Division (STAD) untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Kelas V SD GMIM I Tomohon - Mersty E. Rindengan (Jurnal Ilmiah Wahana Pendidikan, 2021)
The problems found from learning Indonesian both from the students and the deficiencies that exist in the teacher because in the teaching and learning process it is not yet oriented towards students as learning subjects but is still teacher-centered, here the teacher uses more of the lecture method, the teacher does not optimize the learning media other than that teachers also lack mastery of the material as a result students find it difficult to learn and their learning outcomes are relatively low. The lack of motivation given by the teacher is a factor in the lack of student learning outcomes in participating in Indonesian language learning. So it is necessary to apply one of the learning models, namely by using the Student Teams Achievement Division (STAD) learning model. This study aims to improve learning outcomes in Indonesian in class V SD GMIM I Tomohon through the application of the Student Teams Achievement Division (STAD) learning model. The research method used was classroom action research (PTK) which refers to Kemmis and Mc Taggart's design by following four stages: Planning, Action, Observation, and Reflection. Data collection techniques were carried out through observation and tests. Data analysis techniques in this study calculate the percentage of student learning outcomes. The research results were taken from observations and test results carried out in each cycle. The results showed that the learning outcomes of the first cycle reached 69.70%, while the second cycle reached 90.29%. In this case, there was an increase in the learning outcomes of Indonesian students in class V SD GMIM I Tomohon using the Student Teams Achievement Division (STAD) learning model. Thus it can be concluded that the application of the Student Teams Achievement Division (STAD) learning model can improve Indonesian learning outcomes for fifth grade students at SD GMIM 1 Tomohon. So it is suggested to elementary school teachers to be able to apply the Student Teams Achievement Division (STAD) learning model in the learning process